How National Institutions Shape Skilled Immigrants' Chances of Getting Hired: Evidence from Harmonised Factorial Surveys with Employers in Germany and England - Stumpf, Felix [Verfasser]; Damelang, Andreas [Verfasser]; Abraham, Martin [Verfasser]; Ebensperger, Sabine [Verfasser] (My University, 2020)
"This study provides novel insights into the institutional conditions under which skilled immigrants get hired for skilled jobs in different countries. We argue that immigrants' hiring chances depend on the interplay between institutions in sending countries, which determine the type of education that immigrants bring, and institutions in receiving countries, which shape employers' preferences for certain types of education. We develop a research design that considers this interplay and allows us to directly compare how education from sending countries with different institutional arrangements is rated by employers in two countries with widely divergent institutional contexts of reception, Germany and England. Using harmonised factorial surveys, we simulate hiring processes and evaluate the chances of German and English employers inviting foreign-educated immigrants to interviews for jobs commensurate with their education. The survey design makes it possible to experimentally vary the institutional settings in which immigrants acquired their education in the sending country, and isolate their effect on employers' ratings. Our key finding is that immigrants from sending countries with highly standardised occupation-orientated education systems prevail in the hiring competition, irrespective of the education system in the receiving country." (authors' abstract; BIBB-Doku)

"Diese Studie liefert neue Erkenntnisse zu den institutionellen Rahmenbedingungen, unter denen im Ausland ausgebildete Fachkräfte Zugang zu qualifizierten Tätigkeiten erhalten. Wir argumentieren, dass ihre Arbeitsmarktchancen von der institutionellen Ausgestaltung der Ausbildungssysteme im Herkunfts- und Aufnahmeland abhängen. Diese bestimmen einerseits den Typus beruflicher Qualifikationen, die ausländische Fachkräfte mitbringen, und andererseits welche Qualifikationen Arbeitgeber bei der Stellenbesetzung erwarten. Mithilfe eines experimentellen Forschungsdesigns untersuchen wir, wie Arbeitgeber in Deutschland und England, zwei Ländern mit ganz unterschiedlich ausgestalteten beruflichen Systemen, Qualifikationen aus unterschiedlich ausgestalteten ausländischen Systemen bewerten. Für diesen Ländervergleich erheben wir in faktoriellen Surveys, mit welcher Wahrscheinlichkeit die Arbeitgeber ausländische Fachkräfte zum Vorstellungsgespräch für qualifizierte Jobs einladen. Dabei variieren wir experimentell die institutionellen Merkmale der Systeme, in denen Migranten ihre Ausbildung im Herkunftsland erworben haben, um ihre Kausaleffekte auf die Arbeitgeberentscheidungen schätzen zu können. Unsere Ergebnisse zeigen, dass Migranten aus hochgradig standardisierten und berufsspezifischen Ausbildungssystemen bevorzugt werden, und zwar unabhängig vom Ausbildungssystem des Aufnahmelands." (Autorenreferat; BIBB-Doku)
Wie nationale Institutionen die Einstellungschancen ausländischer Fachkräfte prägen - Ergebnisse harmonisierter faktorieller Surveys in Deutschland und England
Keywords: P 1.5 Migranten; I 2.2.1 Westeuropa; Ausländer; Auslandsqualifikation; Arbeitsmarktchance; Einflussfaktor; Berufsbildungssystem; Herkunftsland; Einwanderungsland; Arbeitgeber; England; Bundesrepublik Deutschland